Cultural interconnections: Textile craft and burial practices in Early Medieval Sudan - Yvanez, Elsa; Murillo, Mary Lou; Francigny, Vincent; de Voogt, Alex (Archaeological Textiles Review, 2020)
This article focuses on a loincloth found in situ on the skeleton of an Early Medieval male buried on the Nubian island of Sai, in northern Sudan, dated to the seventh to ninth centuries BCE. This loincloth diff ers from most contemporary textile production because it was woven in a triangular form and probably using threads made from dromedary wool. It exhibits several phases of repair and reuse until its burial with the body. This garment therefore illustrates the textile expertise and clothing practices of the ancient Nubians, as well as the cultural role of textiles in funerary rituals.